2022
DOI: 10.1111/rda.14270
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the metabolome of seminal plasma in two different horse types: Light versus draft stallions

Abstract: The application of the ‘omics’ studies in the field of animal reproduction has been aimed at identifying novel biomarkers of fertility since the last few years. When assessing reproductive efficiency in horses, breed should also be taken into account as it can influence semen quality and fertility. Considering the growing interest in metabolomic analysis to evaluate male fertility, we aimed to investigate the metabolomic profile of seminal plasma in two different horse breeds. Twelve healthy stallions, n.6 Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…However, they observed variations in the concentration levels of 18 out of these 28 metabolites. The authors also found that myo-inositol, isoleucine, and valine negatively correlated with progressive motility in donkeys, in agreement with the findings reported in horses by Bazzano et al [52].…”
Section: Pony Mares *supporting
confidence: 90%
See 2 more Smart Citations
“…However, they observed variations in the concentration levels of 18 out of these 28 metabolites. The authors also found that myo-inositol, isoleucine, and valine negatively correlated with progressive motility in donkeys, in agreement with the findings reported in horses by Bazzano et al [52].…”
Section: Pony Mares *supporting
confidence: 90%
“…Studies have been performed on seminal plasma in humans [58][59][60] and in different animal species [61][62][63][64]. Three of them [51][52][53] have focused on equine seminal plasma, providing interesting insights into the metabolites contained in this biofluid. A preliminary study performed by Magistrini et al [51] identified, by 1 H-NMR, metabolites defined as markers of sex gland secretions.…”
Section: Pony Mares *mentioning
confidence: 99%
See 1 more Smart Citation